An observational study of individual child journeys through autism diagnostic pathways, and associated costs, in the UK National Health Service - Male, Ian; Farr, William; Bremner, Stephen; Gage, Heather; Williams, Peter; Gowling, Emma; Honey, Emma; Gain, Aaron; Parr, Jeremy (Frontiers in Rehabilitation Sciences, 2023)
Diagnostic assessment demand for children with possible autism has increased significantly in recent years. Services are under pressure to meet demand in a timely manner, whilst delivering high-quality diagnostic assessment, broadly following National Institute and Care Excellence multidisciplinary assessment guidelines. This UK National Health Service (NHS) study aimed to answer: how many hours of professional time are required to deliver autism diagnostic assessment, and how much does this cost? 488 children recruited, from 22 Child Development Services (CDS), four Child and Adolescent Mental Health Services (CAMHS) and one tertiary centre . Children’s ages ranged 21-195 months (mean 82.9 months, SD 39.36); 87% were either under 5 (36%) or 5 to 11 years (51%). Children seen by CDS were significantly younger than CAMHS assessed (mean (SD) 6.10 (2.72) vs 10.39 (2.97) years, p<0.001); CDS saw all children (0-16 years), CAMHS saw children aged 5+. Mean (SD) days to diagnosis were 375 (235), with large variation (range 41-1553 days). Mean hours of professional time per child was 11.50 (7.03), but varied substantially between services (IQR 8.1-15.0 hours) and individuals within service. Associated mean (SD) cost (British pounds, 2020) of assessment was £846.00 (536.31). Within sample, 339 (70.0%) children received autism diagnosis with or without comorbidity; 54 (11%) received no neurodevelopmental diagnosis; 91 (19%) did not have autism but received alternative neurodevelopmental diagnosis. Modelling showed children with one or more coexisting conditions took longer to diagnose, and assessment was more costly e.g. child assessment with two or more coexisting conditions took an average 117 days longer, cost £180 more than a child where no neurodevelopmental diagnosis was given. Age did not predict days to diagnosis or assessment costs. Typical assessment took 11 hours of professional time over 12-months to complete, costing GB£850 per child. Variation between centres and children reflect differences in complexity of diagnostic presentation. The process needs stremalining. These results give information to those delivering/planning autism assessments using MDT approach, in publicly funded health systems. Planning resourcing of future diagnostic services needs to consider growing demand for assessment, and the need to enable context appropriate assessment for services, and child/family complexity,